Islamic Boarding School Management in the Modern Era: Literature Review of Local Wisdom-Based Management Models - Kasman Kasman (Bulletin of Indonesian Islamic Studies, 2025)
This study analyzes the modern pesantren management model by emphasizing the integration of local wisdom values ​​in institutional governance, especially in pesantren in Mandailing Natal Regency, North Sumatra. Using a qualitative approach that combines a comprehensive literature review and limited field observation, this study found a hybrid management model that integrates contemporary managerial principles with local cultural values ​​such as dalihan na tolu, charismatic leadership of kiai, and the tradition of community mutual cooperation (marsialap ari). The model has been proven to strengthen the character of students, increase social legitimacy, and build institutional resilience in facing the flow of globalization. Although the results are positive, aspects of managerial professionalism, institutional documentation, and technology utilization still need strengthening. These findings enrich the literature on contextual, adaptive, and sustainable pesantren management. Limitations of the study include the narrow geographic scope and the absence of quantitative measurements of model effectiveness; therefore, cross-regional comparative research with mixed methods is recommended to produce a more holistic analysis.